184 WHICH ROUTE FOR ESOPHAGEAL RECONSTRUCTION WHEN NONE IS FEASIBLE?. (14th September 2020) - De Malleray, H; Hubaud, V; Bottet, B; Brioude, G; Trousse, D; Thomas, P; D'journo, X
Abstract: : Which route for esophageal reconstruction when none is feasible? Methods: What is in the video: this 3-minute video describes a challenging case of a complex esophageal reconstruction for a giant trachea-esophageal fistula in a patient with severe comorbidities and a radiation-induced mediastinal fibrosis. We depict the technical aspect of a presternal gastric by-pass covering with a pediculized myocutaneous latissimus dorsi flap. Results: Why this video is important for the congress: this video exposes the surgical dilemma of the route of reconstruction for digestive continuity when none of traditional routes are allowed: 1) posterior mediastinum route forbidden because of post-radiation mediastinal fibrosis; 2) retrosternal route prohibited by a previous coronary artery by-pass; 3) subcutaneous route not feasible because of severe sternal radiodermatis. Conclusion: In conclusion, our case shows that covering the presternal digestive interposition with a locoregional pediculized myocutaneous flap is a valid alternative when others routes have been eliminated. Video: https://drive.google.com/open?id=1SXueOktZU15N8GgG324KJJb1SF-XqPym